Pelatihan Pemanfaatan Free Platform untuk Mengembangkan Penilaian dalam Pembelajaran Daring - Suhartono Suhartono; Ngatman Ngatman; Tri Saptuti Susiani; Moh Salimi; Ratna Hidayah (DEDIKASI: Community Service Reports, 2022)
The free platform is a free application that can be used to evaluate online learning. The problem is that teachers are hampered by using modern free platforms. Teachers still apply conventional assessments, such as printing paper, taking photos of student's work, and sending them via WhatsApp groups. This assistance is intended to describe the results of training on using free platforms to develop assessments in online learning for elementary schools in Kebumen Regency. Servants collaborated with several partners, namely Public Elementary School 4 Kedawung, Public Elementary School 2 Kewayuhan, Public Elementary School 1 Kewayuhan, and Public Elementary School 3 Kewayuhan. The first training was held on June 24, 2021. The service results showed that the preparation aspect had reached a sufficient percentage of 75.4%, while the implementation aspect had a percentage result of 80.1% in the high category. Moreover, the processing aspect reached a sufficient percentage of 75.4 %, and the utilization aspect reached 79% with a good category. From these results, it can be concluded that teachers can follow the procedures for using free platforms (Google Forms and Quizizz) to develop assessments quite well.